Online Donation for Charitable Giving: The Case of Yayasan Kebaikan Ummat - Apriliani, Selvi; Susilawati, Cucu (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
The burgeoning trend of online donations has assumed prominence within society. This research endeavors to elucidate the intricacies involved in the collection, management, and distribution of online donation by Yayasan Sinergi Kebaikan Ummat. It seeks to identify the contractual frameworks employed in the online donation process, while also examining the legal dimensions of online donations through the lens of Sharia Economic Law. The type of this research is qualitative. Data collection techniques encompass indirect observation, interviews, and documentation review. The data analysis is underpinned by the premise that muamalah activities, whether conducted directly or indirectly, are permissible unless explicitly proscribed. The legal framework governing muamalah derives from the Qur'an and Hadith, which establish the principles congruent with Sharia, aimed at fostering societal justice. The findings of this research reveal that Yayasan Kebaikan Ummat, acting as a campaigner, assumes the role of a third-party intermediary in the donation process. Here, the donor represents the first party, while the online platform serves as the second party. The process of raising donations involves several contractual arrangements, including ijarah, wakalah bil ujrah, and jualah contracts, all of which entail the provision of wages (ujrah). The administration fee established by the platform, termed ujrah, serves as compensation for the campaigner's fundraising assistance. Consequently, online donations facilitated through these platforms are permissible, primarily due to the incorporation of the tabarru' contract within the arrangement.